## ryanpauls Group Title Solve the equation. Check the solution. -2/(x+4) = 4/(x+3) a. -13/6 b. -11 c. -8/3 d. -11/3 one year ago one year ago

1. ryanpauls

also could you show your work? I am not sure how to do this because of the equal sign

2. ZeHanz

Use the rule:$\frac{ a }{ b }=\frac{ c }{ d } \Leftrightarrow ad=bc$so: -2((x+3)=4(x+4) expand the brackets, collect like terms and solve for x.

3. FibonacciChick666

so first relieve yourself of the fractions by multiplying the denominators on both sides and get: $-2/(x+4)=4/(x+3)$ $-2(x+3)=4(x+4)$ now distribute the -2,4 $-2x-6=4x+16$ finally solve for x by combining like terms $-2x=4x+16+6$ $-6x=22$ $x=-22/6$ this reduces to $x=-11/3$ therefore our answer is d.

4. ryanpauls

thanks! i just tried it out like that and I got the same answer.

5. FibonacciChick666

do you understand the process?

6. ryanpauls

yes

7. FibonacciChick666

good! =D

8. ryanpauls

what about: Simplify the sum (x-2)/(x+3) + (10x)/(x^2-9) I have this: (x-2)/(x+3) + (10x)/(x+3)(x-3) I know the x+4 cancels out, but what do I do to the top?

9. ryanpauls

i meant x+3 cancels out

10. FibonacciChick666

ok so what you want to do is multiply the first fraction by a fraction that simplifies to 1. pick something that gives you the same denominator